The Development of Hydraulic Robotic Arm as a STEM-Based Physics Learning Media - Lestari, Isti Fuji; Muhajir, Siti Nurdianti (STKIP Singkawang, 2024)
The aim of this research is to develop, assess feasibility, and determine students responses of hydraulic robotic arm as a STEM-based physics learning media. The method used in this research is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) framework. Expert validation results show that the content's feasibility percentage is 95% (very good) and the media's feasibility is 94% (very good). The experiment was conducted involving 155 secondary school students in Garut, yielding a trial outcome of 84%. The results of the research indicate that the hydraulic robotic arm is suitable for use as a STEM-based physics learning media both in terms of content and the learning media. Additionally, students responses to the hydraulic robotic arm are categorized as good, particularly in terms of its benefits in learning.